Fate shapes One’s Destiny in Monica Ali’s Brick Lane (2003) – A Sociological and Literary Analysis – - Bahaa El-Din, Hany Mohamed; Rezk, Walid Abdallah (Journal of Humanities & Social Sciences, 2021)
This paper aims at analyzing Brick Lane (2003) Monica Ali’s masterpiece which is regarded as a very good example of post-colonial literature with its main characteristics of displacement, racism, diaspora, hybridity and alienation and exploring its main theme, how fate shapes one’s destiny which is directly related to immigrating from homeland for better social and economic conditions. This theme starts at the very beginning with the main character Nazneen, when she was born as a sick child, the midwife told her mother that she could take the baby to hospital, or just let her to her fate. Nazneen’s mother chose to wait and see what might happen to her child. During their getting older, Nazneen and her sister Hasinaa learned that fighting fate would be risky and fatal. Monica Ali’s Brick Lane is a novel that has nearly all the components of a real diasporic heroine that passes through the complicated dilemma of adapting to a multicultural community. This paper is intended to prove that this novel can be regarded as a very good example of post-colonial literature and how the writer is able to present the Asian heroine who has always been marginalized throughout the different ages.